The Relationship Between Hemoglobin Levels And Quality of Life (QoL) Among Adolescent Girls in The Working Area of Tengah 1 Singkawang Public Health Center - Ria Anggreni; Febry Mutiariami Dahlan; Putri Azzahroh (International Health Sciences Journal, 2026)
Anemia is becoming more common among teenage girls worldwide, including in Indonesia. Complications like chronic stress and exhaustion, which can result in weakness, dizziness, blurred vision, and a pale face, are among the clinical signs that can arise when the Hb level falls below the normal range. A person's perception of their place in daily life in relation to the culture and values of their community, as well as their own objectives, expectations, desires, and concerns, is known as their quality of life (QoL). The purpose of this study is to ascertain the connection between adolescent girls' quality of life and hemoglobin levels in the Singkawang Tengah 1 Public Health Center's service area. This study combines analytical quantitative research with descriptive-correlational research. This study is cross-sectional, descriptive-correlational, and of the analytical quantitative research type. This study's sample was drawn from the entire population of 110 respondents using total sampling. The WHOQOL-BREF questionnaire and an HB meter for measuring hemoglobin levels were the tools used in this investigation. The chi-square test was used to analyze the data. The study's findings show that hemoglobin levels and teenage girls' quality of life are significantly correlated (p<0.05), with a value of 0.000. The quality of life of teenage girls is found to be correlated with hemoglobin levels.